Combination of Andisol Soil-Bioball-Bacillus sp. For Cadmium Removal Application - Ratna Tri Widyawati; Pranoto Pranoto; Edi Pramono (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Industrial growth in Indonesia, especially the metal industry, has the potential to produce waste that can pollute the environment and hurt humans, animals, and plants. One of these pollutants is heavy metal cadmium (Cd). Besides that, cadmium is very toxic and will cause serious illness for humans. Bacillus sp. is a potential bacterium that can remove harmful substances so that it can be used for bioremediation. However, the ability of Bacillus sp. to absorb cadmium has not been reported. The research aims to study the effectiveness of optimal pH conditions in absorbing heavy metal cadmium. An adsorbent with composition andisol soil: bioball: Bacillus sp. 2:0:0; 1.5:1:4.3×105; 1:2:8.2×105; 0.5:3:1.21×106; and 0:4:1.58×106 (gr:piece:(cell/mL)) put into a beaker containing 100 mL of 6 ppm Cd solution with various pH 1, 2, 3, 4, 5, and 6. The aerator was added at a constant speed for 60 minutes. After 60 minutes, the Cd content was analyzed using Atomic Absorption Spectroscopy (AAS). The combination of andisol, bioball, and Bacillus sp. can absorb cadmium at the optimum conditions of pH 5, with composition andisol: Bioball soil: Bacillus sp. 1.5:1:4.3×105 (g:piece:(cell/mL)), and contact time of 120 minutes with total removal of 75.6%.